Comedy writing for television and Hollywood - Josefsberg, Milt 1911-
Discusses jokes, puns, monologues, rhythm, repetition, role reversal, visual humor, juxtaposition, character, and plot lines and includes advice about partnerships, rejection, criticism, censorship, and revisions.